Cytochrome P450 Sterol 14 Alpha-Demethylase Gene SsCI72380 Is Required for Mating/Filamentation and Pathogenicity in Sporisorium scitamineum - Li, Huizhong; Cai, Yichang; Deng, Quanqing; Bao, Han; Chen, Jianwen; Shen, Wankuan (Frontiers in Microbiology, 2021)
Sugarcane smut is a significant sugarcane disease caused by Sporisorium scitamineum and is a large threat to the sugar industry in China and the world. Accordingly, it is important to study the pathogenic mechanism by which this disease occurs to identify effective prevention and control strategies. Gene SsCI72380, which encodes cytochrome P450 sterol 14 alpha-demethylase (CYP51), was screened out from the transcriptome of S. scitamineum. In this study, the functions of gene SsCI72380 were identified via the knockout mutants ΔSs72380+ and ΔSs72380-, which were obtained by polyethylene glycol-mediated protoplast transformation technology, as well as the complementary mutants COM72380+ and COM72380-. The results showed that the CYP51 gene SsCI72380 played an important role in sporidial growth, sexual mating/filamentation, hyphae growth, and pathogenicity in S. scitamineum. Gene SsCI72380 may regulate the structure and function of the cell membrane by encoding CYP51 enzymes and then affecting the biosynthesis process of ergosterol on the cell membrane. Gene SsCI72380 also played an important role in the response toward different abiotic stresses, including hyperosmotic stress, oxidative stress, and cell wall stress, by regulating the permeability of the plasma membrane. In addition, gene SsCI72380 is a new type of pathogenic gene from S. scitamineum that enhances the pathogenicity of S. scitamineum.